Hubungan Kejadian Perilaku Bullying Verbal dengan Tingkat Stres (Korban) pada Remaja Putri - Tika Fitriyani; Wahyu Endang Setyowati; Betie Febriana (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Adolescence is a time of fast physical and psychological development. Between the ages of 10 and 19, adolescence takes place during the childhood and adulthood periods. Teenagers are particularly susceptible to abnormal behavior, such as bullying. Bullying is common in schools and can be brought on by bad settings or family dynamics. The effects of bullying behavior include tension, anxiety, and sadness. Stress usually occurs where bullying demands are usually like cognitive environments, personality. Untreated stress in teenagers can result in substance abuse, suicidal thoughts, and other negative interactions. Method: This study uses a cross-sectional technique and is classified as quantitative research. Female students from SMP Islam Sultan Agung 4 Semarang served as the sample. Simple random sampling was the method employed, with 114 participants. The chi square test was the correlation test employed in this investigation. Results: Based on the results of the analysis, it was obtained that of the 114 respondents, most of them had age characteristics of 13 years as many as 51 or 44.7%, and were female as many as 114 or 100.0%. According to the study's findings, 67.5% of female students reported having high stress levels, while 63.2% reported moderate verbal bullying. A p value of 0.035 was revealed by statistical testing that used the chi square test. Conclusion: Stress levels (victims) and the prevalence of verbal bullying behavior in female teenagers are closely correlated (p value 0.035).